ОЦЕНКА ГРАНИЧНЫХ УСЛОВИЙ ФОРМИРОВАНИЯ РУСЕЛ РАЗНЫХ ТИПОВ НА РЕКАХ АЛТАЙСКОГО РЕГИОНА (БАССЕЙН ВЕРХНЕЙ ОБИ) - Смирнова В.Г.; Чалов Р.С. (My University, 2004)
On the base of QI-diagram analysis the formation of different types of channels was considered: for plain rivers, mountain rivers, incised rivers and rivers with broad flood plain. Heterogeneous approximations of boundary lines, dividing point fields on the QI-diagrams, corresponding to different channel types, were revealed. Authors argue that incised channels appear at maximal intensity of flow; branching channels occur on rivers with average maximum discharge more than 50 m 3/sec, which is characteristic for big rivers.
Keywords: 551.435.11(282.251.1)